Provincial Patronage Networks & Small Businesses in the Greater Mekong Sub-Region (GMS): Implications for the ASEAN Economic Community (AEC) 2015 - Sujarittanonta, Lavanchawee (Information Management and Business Review, 2014)
In East Asian cultures such as Thailand, existing patronage in local political and administrative structures can limit the ability of the state to affect its policies. Consequently, this research examines the extent to which these â€œguanxiâ€ networks affect provincial small businesses, which lack the resources to persuade local provincial patronage providers to advantage them. This has implications for the ASEAN Economic Community, when cross-border economic activity is expected to increase, especially in the Greater Mekong Sub-region (GMS). Thailand is chosen for this study because of its long history of strong power patronage systems at the provincial level and for its regional economic prominence and rich cross-border trade activities with neighboring countries such as Laos, Myanmar, Cambodia and Malaysia in the GMS. Findings from interview-based data collected from 178 small firm respondents from 31 provinces suggest that â€œfriends and family guanxiâ€ networks matter most for provincial small businesses. While there is an ongoing relationship between political officers and top managers of buyer (not supplier) firms, these are likely to be large firms, not small firms. Consequently, it is likely that small provincial firms, whether Thai or from neighboring countries, will not need to foster connections with local politicians and government officials.